A facile synthesis of nanocrystalline anatase TiO2from TiOSO4aqueous solution - Songpon Ngamta (2018)
A green and simple synthetic route via a thermal hydrolysis of titanyl sulphate (TiOSO 4 ) has been employed to prepare nanocrystalline anatase titanium dioxide (TiO 2 ) without further calcination. X-ray diffraction (XRD) clearly showed that the anatase crystalline structure was already formed under the reaction conditions at 80.0±2.0 C. The obtained anatase TiO 2 showed high thermal stability as the anatase-to-rutile transformation in only 25 wt% occurred at 900 C. Scanning electron (SEM) and transmission electron (TEM) micrographs revealed that TiO 2 secondary particles comprised irregular primary particles with diameters of 8-22 nm depending on the calcination temperature. Superior UV-light absorption intensity compared with the commercial P25 TiO 2 suggested the great potential of the obtained material for use as a highly efficient photocatalyst under UV irradiation. © 2013 Elsevier B.V.